Phytase and sodium diformate supplementation in a plant‐based diet improves protein and mineral utilization in rainbow trout (Oncorhynchus mykiss). (4th September 2015) - Morales, G.A.; Denstadli, V.; Collins, S.A.; Mydland, L.T.; Moyano, F.J.; Øverland, M.
Abstract: A basal isonitrogenous and isoenergetic plant‐based diet (Control) was supplemented with either 10 g kg −1 sodium diformate (NaDF), 4000 FTU kg −1 phytase (Phy) or a combination of both additives (NaDF + Phy). Three hundred juvenile rainbow trout with an average weight of 120 g were randomly distributed into 12 fibreglass tanks (300 L). After 65 days of trial, fish fed diets containing phytase, NaDF or the combination of both additives showed a higher growth rate ( P  <   0.05) compared to fish fed Control diet. NaDF increased feed intake ( P  =   0.032), while phytase inclusion resulted in a better feed conversion ratio ( P  <   0.0001) and a higher N retention efficiency ( P  =   0.02) compared with the Control. Apparent digestibility of P, Ca, Mg and Zn was improved by the use of phytase ( P  <   0.005) as well as P, Ca and Mg retention efficiency in fish ( P  <   0.0001). Using 4000 FTU kg −1 phytase in plant‐based diets resulted in a 13% and 50% reduction in N and P loadings, respectively. The use of NaDF in combination with phytase in a plant‐based diet for rainbow trout resulted in a higher weight gain than that when NaDF was used alone.